Implementation Of Qr-Code Based Point Of Sales Application For Retail Store - Simeon Bensona; FX Hendra Prasetya; Bernadinus Harnadi (Journal of Business and Technology, 2022)
Point of Sales is an application used to record transactions. This application can be used to help business owners including retail stores, self-service stores, and even supermarkets so that every transaction can be supervised and tracked. This kind of application gives convenience and easiness to avoid as many as possible from transaction fraud that may happen in running the business. This kind of application has features that may fulfill the direct and in-direct needs in business transactions. POS Applications can now be installed and operated in any kind of common electronic device in society including but not limited to laptops, smartphones, and personal computers. Because of the developments of technologies, the use of cameras in every device has become common nowadays. In the context of technology, this new feature can be utilized to search and find data and even read the data in the system. To store data in the real world, the use of QR-Code has been becoming common but rarely been implemented in POS Application. Because of this kind of capability, the three of these technologies can be integrated to ease the human’s works. Several problems in business need contributions like this.  In order to prove that, this research had been conducted to a retail shop by implementing Point of Sales Application and doing interviews to collect data as proof of the hypothesis. In order to do that, the research will be started to ask several questions about the needs of the business and build the application using Rapid Application Development Methodology. Rapid Application Development Method will be using the data from the interview as the requirements of system development. The Rapid Application Development Methodology was used because it has effectiveness and efficiency to build applications without wasting time and efforts in building useless features. After the application is done, then the testing will be conducted by listing all main features of the application and checking whether the application works as expected. When the testing is done, the implementation of application will be conducted directly to the business. Implementation will be meeting several issues and revisions, in this section, another interview will be conducted in order to gather information about anything that needs to be fixed or changed. After the last interview was conducted, several facts were found. It proves that what has been stated in previous research was correct. Research has found that fraud and human error that spoil the business has occurred.